Impacts of El Niño Southern Oscillation on the global yields of major crops - Iizumi T; Luo J; Challinor, Andrew J.; Sakurai G; Yokozawa M; Sakuma H; Brown, M.E.; Yamagata T (Springer, 2014)
The monitoring and prediction of climate-induced variations in crop yields, production and export prices in major food-producing regions have become important to enable national governments in import-dependent countries to ensure supplies of affordable food for consumers. Although the El Niño/Southern Oscillation (ENSO) often affects seasonal temperature and precipitation, and thus crop yields in many regions, the overall impacts of ENSO on global yields are uncertain. Here we present a global map of the impacts of ENSO on the yields of major crops and quantify its impacts on their global-mean yield anomalies. Results show that El Niño likely improves the global-mean soybean yield by 2.1—5.4% but appears to change the yields of maize, rice and wheat by −4.3 to +0.8%. The global-mean yields of all four crops during La Niña years tend to be below normal (−4.5 to 0.0%). Our findings highlight the importance of ENSO to global crop production.